DIGESTIBILITY NUTRIENT OF COMMERCIAL RATIONS SUBSTITUTED WITH DUCKWEED (Lemna minor) FERMENTED BY Saccharomyces cerevisiae IN BROILER - I K. E. A., Putrayasa; Mahardika, I G.; Sudiastra, I W. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the effect of adding Duckweed fermented by Saccharomyces cerevisiae in commercial ration on broiler digestibility. The research design used was a Completely Randomized Design (CRD) consisting of four treatments and four replications, each replication containing four broilers. The treatment given is feed without additive duckweed fermented (P0/kontrol); feed with 5% duckweed fermented (P1); feed with 10% duckweed fermented (P2) and feed with an 15% duckweed fermented (P3). The variables observed were dry matter digestibility, organic matter, crude protein and crude fiber digestibility. The results showed that broilers were given duckweed fermented by Saccharomyces cerevisiae at a rate on 5%, 10% and 15% showed decreased digestibility of dry matter, organic matter, crude protein and crude fiber. So that it can be concluded the adding of duckweed fermented by Saccharomyces cerevisiae at a rate on 15% reduced the digestibility of dry matter, organic matter crude protein and crude fiber in broilers.